Effect of an Eye Health Education Program on Older African Americans' Eye Care Utilization and Attitudes about Eye Care - Owsley, Cynthia (2013)
We examined the impact of an eye health education program for older African Americans on attitudes about eye care and utilization, using a randomized trial design in a community setting. Participants were older African Americans attending activities at senior centers. Ten centers were randomized to an eye health education (InCHARGE(©)) or social-contact control presentation. InCHARGE(©) addressed the importance of annual dilated comprehensive examination and strategies reducing barriers to care. The control presentation was on the importance of physical activity. Outcomes were attitudes about eye care through questionnaire 6 months post-event, and eye care utilization during 12 months post-event through medical record abstraction. At baseline > 80% participants in both arms said transportation and finding, communicating, and trusting a doctor were not problematic and agreed that yearly care was important. One-fourth said eye examination cost was problematic; one-half said spectacle cost was problematic. There were no group differences 6 months post-event. During 12 months pre-event, dilated exam rate was similar in the groups (38.3% InCHARGE(©), 40.8% control), and unchanged during 12 months post-event. Results suggest less than half of older African Americans received annual dilated eye care. Group-administered eye health education did not increase this rate. Even before the program, they had positive attitudes about care, yet many cited examination and spectacle cost as problematic, which was not mitigated by health education. Evidence-based strategies in a community setting for increasing eye care utilization rate in older African Americans have yet to be identified. Policy changes may be more appropriate avenues for addressing cost.